1997
DOI: 10.1037/0096-1523.23.3.768
|View full text |Cite
|
Sign up to set email alerts
|

The line–motion illusion: Attention or impletion?

Abstract: When a brief lateral cue precedes an instantaneously presented horizontal line, observers report a sensation of motion in the line propagating from the cued end toward the uncued end. This illusion has been described as a measure of the facilitatory effects of a visual attention gradient (O. Hikosaka, S. Miyauchi, & S. Shimqjo, 1993a). Evidence in the present study favors, instead, an account in which the illusion is the result of an impletion process that fills in interpolated events after the cue and the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
144
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(157 citation statements)
references
References 24 publications
9
144
4
Order By: Relevance
“…For example, when the stimulus configuration shown in Figure 10, Image 1, is replaced all at once by Image 2a, motion inward from both the left-hand cue and the right-hand cue is perceived. However, if Image 1 is replaced all at once by Image 2b instead of Image 2a (Tse et al, 1996(Tse et al, , 1998; see also Downing & Treisman, 1997), then the percept between the cues is very different. Now the line between the cues undergoes TAM entirely away from the left-hand cue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when the stimulus configuration shown in Figure 10, Image 1, is replaced all at once by Image 2a, motion inward from both the left-hand cue and the right-hand cue is perceived. However, if Image 1 is replaced all at once by Image 2b instead of Image 2a (Tse et al, 1996(Tse et al, , 1998; see also Downing & Treisman, 1997), then the percept between the cues is very different. Now the line between the cues undergoes TAM entirely away from the left-hand cue.…”
Section: Discussionmentioning
confidence: 99%
“…According to their model, when the initial spot appears, an attentional gradient forms around the spot; when the line appears all at once, portions of the line nearer the attended spot enter a motion detecting mechanism before portions of the line that lay farther away from the attended location. Other authors (Downing & Treisman, 1995, 1997Kawahara, Yokosawa, Nishida, & Sato, 1996;Tse & Cavanagh, 1995;Tse, Cavanagh, & Nakayama, 1996, using more complex first and second image shapes, challenged the attentional prior entry account. They argued instead that illusory line motion was actually a variant of translational apparent motion (e.g., Anstis, 1980;Braddick, 1980;Dawson, 1991;Wertheimer, 1912Wertheimer, /1961.…”
Section: The Duration Of 3-d Form Analysis In Transformational Apparementioning
confidence: 99%
“…However, perhaps a weak ILM experience is generated by endogenous cues but the real line drawing and strong ILM generated from the peripheral cues produced such strong motion experiences that any endogenously generated ILM was, by comparison, overwhelmed. Indeed, some previous studies that reported ILM induced by endogenous orienting also reported effects smaller than those found with exogenous orienting (P. E. Downing & Treisman, 1997;Schmidt, 2000). We tested this "adaptation level" possibility in Experiment 3 by never presenting a strong line motion perception within the context of the experiment.…”
Section: Experiments 3a-3cmentioning
confidence: 99%
“…One leading explanation for the illusion (Hikosaka, Miyauchi, & Shimojo, 1993a, 1993bSchmidt & Klein, 1997) is based on the idea that there is a gradient of accelerated arrival times at perceptual levels of processing around a cued location and that, when a line is presented (all at once) across this gradient, the difference in arrival times across the line is interpreted by motion perception systems as a drawing of the line over time. Although there are some notable exceptions to this view (e.g., P. E. Downing & Treisman, 1997;Tse & Cavanagh, 1995), it does serve as a general framework for the research presented here.…”
mentioning
confidence: 99%
See 1 more Smart Citation